Adherence to treatment in pulmonary tuberculosis: Rodgers’ evolutionary concept analysis - Prasetyo, Yunus Adhy; Thanasilp, Sureeporn; Preechawong, Sunida (Belitung Nursing Journal, 2024)
Background: Adherence to treatment is essential for the management of pulmonary tuberculosis. Nurses and healthcare professionals play a significant role in promoting adherence behavior among this population. Nevertheless, defining adherence to treatment within this particular population remains complex. Objective: This study aimed to explore and clarify the concept of adherence to treatment among individuals with pulmonary tuberculosis. Methods: Rodgers’ evolutionary concept analysis was employed in this study. A literature search was conducted in the PubMed and Scopus databases to identify relevant studies published between July 2013 and July 2023. Results: The attributes of adherence to treatment in pulmonary tuberculosis consist of multiple components: biological, individual, social, health service, and policy-making processes. Antecedents include various patient-related factors as well as factors associated with clinical conditions and patient-health professional engagement. Three consequences of the concept have emerged: enhanced treatment efficacy, increased commitment to tuberculosis treatment adherence, and improved health service quality. Conclusion: This study provides a comprehensive operational definition of adherence to tuberculosis treatment, including its attributes, antecedents, and consequences. This framework will assist nurses in evaluating adherence more effectively. However, further research into the experiences of individuals adhering to tuberculosis treatment is needed to confirm and enhance these strategies.